Baqer Turki Al-lamey Voltage Profile Enhancement and Losses Reduction at Future Expansion of Transmission power Systems - Turki, Baqer (University of Thi-Qar Journal of Science, 2019)
The current paper presents flexible and feasible method for enhance the voltage profile in some buses and reduction of the losses in overall transmission power system ifthe power system subjected to an additional resultant loads in future or current increasing of loads at one or more buses in that power system. The proposed method include estimating the injected MVARs which are required to avert voltage collapse as well as reduction the real power losses. This method is tested by computer simulation implemented on IEEE 30-bus, 41-line transmission power system using MATLAB ToolBox (Ver. 7.5) based on fast decoupled load flow analysis and satisfactory results are obtained. The current paper presents flexible and feasible method for enhance the voltage profile in some buses and reduction of the losses in overall transmission power system if the power system subjected to an additional resultant loads in future or current increasing of loads at one or more buses in that power system. The proposed method include estimating the injected MVARs which are required to avert voltage collapse as well as reduction the real power losses. This method is tested by computer simulation implemented on IEEE 30-bus, 41-line transmission power system using MATLAB ToolBox (Ver. 7.5) based on fast decoupled load flow analysis and satisfactory results are obtained.